2021
DOI: 10.5617/adno.7821
|View full text |Cite
|
Sign up to set email alerts
|

Preservice teachers’ reflections on diversity and on teaching diverse pupils in Norwegian compulsory school

Abstract: The purpose of this study is to investigate how preservice teachers reflect on diversity and on teaching pupils from diverse backgrounds. Following a qualitative research design, the empirical data were constructed through focus group interviews with pre­service teachers attending a 4-year initial teacher education programme for compulsory school in Norway. The thematic analysis of focus group interviews yielded three main results, namely differences are individual and considered natural, diversity as a value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…For these reasons, Tavares (2023) concludes by stressing the need for the development of a practical experience with a more concrete focus on diversity. The importance of establishing a strong link between theory and practice in teacher education programs was also mirrored in the study of KC and Ohna (2021). The participants pinpointed a discrepancy between their et al (2022, 2023) highlighted the need of adopting multilingual pedagogies with teacher and student participants stressing the benefits that can be derived from such practices not only in language learning but also in content classrooms.…”
Section: Multilingual Pedagogies In Norwaymentioning
confidence: 96%
See 1 more Smart Citation
“…For these reasons, Tavares (2023) concludes by stressing the need for the development of a practical experience with a more concrete focus on diversity. The importance of establishing a strong link between theory and practice in teacher education programs was also mirrored in the study of KC and Ohna (2021). The participants pinpointed a discrepancy between their et al (2022, 2023) highlighted the need of adopting multilingual pedagogies with teacher and student participants stressing the benefits that can be derived from such practices not only in language learning but also in content classrooms.…”
Section: Multilingual Pedagogies In Norwaymentioning
confidence: 96%
“…Empirical data from Norwegian classrooms underlined the need for more concrete and practical multilingual training. Recent research (KC and Ohna, 2021;Lorenz et al, 2021;Neokleous et al, 2022Neokleous et al, , 2023Tavares, 2023;Vikøy and Haukås, 2023) revealed that EAL teachers were reluctant to integrate multilingual pedagogies because of either insufficient teacher training on the topic or lack of knowledge and adequate teaching materials. The participants in the study of Tavares (2023) cast a critical eye on the emphasis that their teacher education training placed on the theoretical perspectives of the concept of diversity and multilingualism and the lack of focus on how to put these theories into practice.…”
Section: Multilingual Pedagogies In Norwaymentioning
confidence: 99%
“…However, culturally diverse classrooms represent opportunities for student learning about different cultures, norms, and values alongside academic learning, which is important for overcoming discrimination, exclusion, prejudice, stereotypes and racism, and promoting interaction between students from different cultures. According to previous research, the promotion of such interaction presupposes an acceptance of diversity among the students in the class (KC & Ohna, 2021;Solbue et al, 2017). Moreover, learning to work together in a pluralistic society has been emphasised as important (Gay, 2018).…”
Section: Introductionmentioning
confidence: 99%